SYMBOLIC INTERACTION OF K-POP LOVERS IN THE KOREAN DANCER COMMUNITY IN BANDUNG - Roni Mulyana; Agus Garnida; Hendri Pramadya (Media Inovasi Pendidikan dan Publikasi, 2024)
Korean Pop or what we often hear is K-Pop is a pop music genre originating from South Korea. Korean Pop and Korean Drama are two inseparable aspects of the Korean Wave, which has spread to various countries, one of which is Indonesia. With the very rapid development of technology, it makes it easier for people to obtain information, one of which is the spread of Kpop music. Dress styles, dance styles and KPop music cause teenagers to become fanatical about the Kpop idols they idolize. Bandung, with its wealth of creativity, also has a community of Korean lovers. Initially this community was formed through the Line group as an information medium. This KPop Dancer Group is called ethereal. This community was formed as a forum for those who like KPop. This qualitative research uses a symbolic interactionism approach which seeks to understand human behavior from the subject's perspective. The results of this research obtained are ethereal symbolic interaction patterns which are divided into two, namely verbal and non-verbal symbols. Verbal symbols such as popular Korean words and symbols used by K-Popers dancers in interacting with their identity such as pins, clothes and also attributes used when participating in events.